(untitled) (The International Journal for Scientific Research, 2025)
Purpose: The study aimed to examine the validity of the legislator’s intervention by stipulating provisions regulating the use of artificial intelligence applications in administrative tasks. It also aimed to clarify who is administratively responsible for errors committed by these applications, and to determine the extent to which the administrative legislation in force in Palestine keeps pace with the reality of artificial intelligence. Methodology: The researcher used the analytical inductive approach in the study, beginning with a historical overview of artificial intelligence, then clarifying its concept and applications. It then extrapolated the elements of administrative liability according to administrative jurisprudence and analyzed them in a manner consistent with the use of artificial intelligence applications in administrative work. Findings: The study concluded that artificial intelligence applications may, in the future, reach a stage where their creators or programmers cannot control them, which will lead to the possibility of them committing administrative errors. Furthermore, the Palestinian Administrative Courts Law by Decree No. (41) of 2020 and its amendments do not contain any provisions regulating the use of artificial intelligence applications in administrative work, and the Palestinian legal system is devoid of any text regulating the provisions of artificial intelligence. Administrative liability for errors in AI applications could also fall on the administration, the programmer, or the operator. If the legal personality of AI applications is recognized, there could be administrative liability for these applications. Recommendations: The study recommends the enactment of legislation in Palestine that includes provisions regulating the operation of AI applications in the administrative field and all other fields. It is necessary to recognize the legal personality of these applications as a proactive step against any future developments that may make them difficult to control. It is also necessary to intensify efforts aimed at training public employees on how to handle AI applications in administrative work. In addition, attention should be given to AI, following the example of countries that have shown interest in its use in all fields, while ensuring adherence to AI ethics by companies that manufacture and program its applications.